Public perception on active aging after COVID-19: an unsupervised machine learning analysis of 44,343 posts - Chen, Peipei; Jin, Yuwei; Ma, Xinfang; Lin, Yan (Frontiers in Public Health, 2024)
The aim of this report is to analyze public perceptions of active aging in China on mainstream social media platforms to determine whether the "14th Five Year Plan for the Development of the Aging Career and Elderly Care System" issued by the CPC in 2022 has fully addressed public needs. The original tweets posted on Weibo between January 1, 2020, and June 30, 2022, containing the words "aging" or "old age" were extracted. A bidirectional encoder representation from transformers (BERT)-based model was used to generate themes related to this perception. A qualitative thematic analysis and an independent review of the theme labels were conducted by the researchers. The findings indicate that public perceptions revolved around four themes: (1) health prevention and protection, (2) convenient living environments, (3) cognitive health and social integration, and (4) protecting the rights and interests of the elderly. Our study found that although the Plan aligns with most of these themes, it lacks clear planning for financial security and marital life. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership. References should not be cited in the abstract. Leave the Abstract empty if your article does not require oneplease see the "Article types" on every Frontiers journal page for full details.